Body Mass Index, Physical Activity, Sedentary Behavior, Sleep, and Gross Motor Skill Proficiency in Preschool Children From a Low- to Middle-Income Urban Setting - Tomaz, S.A.; Prioreschi, A.; Watson, E.D.; McVeigh, Joanne; Rae, D.E.; Jones, R.A.; Draper, C.E. (2019)
BACKGROUND: Limited research reports on the relationship between body mass index (BMI) and physical activity (PA), sedentary behavior (SB), sleep, and gross motor skills (GMS) in low- and middle-income countries. The aim of this study was to (1) describe BMI, PA, SB, sleep duration, and GMS proficiency in South African preschool children and (2) identify relationships between variables. METHODS: BMI, including z scores for height, weight, and BMI were determined. Seven-day PA, SB, and sleep were measured using accelerometry. GMS were assessed using the Test of Gross Motor Development (second edition). Associations were explored by comparing sleep, PA, SB, and GMS between BMI tertiles using the Kruskal-Wallis test. RESULTS: Most (86%) children (n = 78, 50% boys) had a healthy BMI (15.7 [1.3] kg/m2). Children spent 560.5 (52.9) minutes per day in light- to vigorous-intensity PA and 90.9 (30.0) minutes per day in moderate- to vigorous-intensity PA; most (83%) met the current PA guideline. Nocturnal sleep duration was low (9.28 [0.80] h/d). Although daytime naps increased 24-hour sleep duration (10.17 [0.71] h/d), 38% were classified as short sleepers. Around half (54.9%) of participants complied with both PA and sleep guidelines. No associations between variables were found. CONCLUSION: Despite being lean, sufficiently active, and having adequate GMS, many children were short sleepers, highlighting a possible area for intervention.